Exploiting online environment to engage customers: social commerce brand community. Issue 3 (20th February 2020) - Cuomo, Maria Teresa; Mazzucchelli, Alice; Chierici, Roberto; Ceruti, Francesca
Abstract : Purpose: Taking jointly into account social commerce and online brand community, this paper aims to investigate how the growth of social commerce and the fast adoption of online brand communities have given firms the opportunity to establish a new kind of community, namely, the social commerce brand community. Adopting a managerial perspective, the research aims to identify the core dimensions of social commerce brand community and shed light on how they contribute in engaging customers and transform them into brand advocates. Design/methodology/approach: Five social commerce retailers operating into five different sectors of activity have been involved in a multiple case study. Data retrieved from semi-structured interviews have been triangulated with information gathered from different sources to provide depth to the cases and enhance data validity. Findings: This study substantiates the rise of social commerce brand community as a new phenomenon that differs from traditional online brand communities and provides firms with concrete support in selling activities and in managing relationships with customers. The multiple case study allows also to detect social commerce brand community core pillars, namely, participants' identification, participation, conversation and social support. These four elements turned out to be crucial to develop an effective social commerce brand community. Research limitations/implications: This study extends existing theory on social commerce and online brand community by investigating the social commerce brand community as a new phenomenon and clarifying the fundamental pillars on which it relies. Originality/value: This study extends existing theory on social commerce and online brand community by investigating the social commerce brand community as a new phenomenon and clarifying the fundamental pillars on which it relies.